2017
DOI: 10.1111/ajo.12681
|View full text |Cite
|
Sign up to set email alerts
|

Mode of delivery for singleton extreme preterm breech fetuses: A 10 year retrospective review from a single tertiary obstetric centre

Abstract: Caesarean section for singleton extreme preterm breech delivery is associated with reduced perinatal mortality, improved neonatal condition at delivery, and increased short-term maternal morbidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 15 publications
0
21
0
Order By: Relevance
“…The Term Breech Trial has had a significant negative impact on the rates of vaginal breech deliveries . While some breech deliveries are planned and known in advance, occasionally there are breech presentations diagnosed unexpectedly in labour.…”
Section: Discussionmentioning
confidence: 99%
“…The Term Breech Trial has had a significant negative impact on the rates of vaginal breech deliveries . While some breech deliveries are planned and known in advance, occasionally there are breech presentations diagnosed unexpectedly in labour.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, mortality in the delivery room appears to be associated mainly with an excess number of complications that are strongly related to breech presentations [ 21 ]. Although these risks have been mentioned by others [ 14 , 16 , 17 ], our study is original in highlighting the cause of this excess mortality in the delivery room.…”
Section: Discussionmentioning
confidence: 80%
“…First, the groups compared retrospectively are far from identical in terms of gestational age and birth weight (aged a few days extra, but very often severely stunted in the PCD group). This is common to all retrospective studies of this type [ 14 , 15 , 19 ]. Secondly, our retrospective study covers a 19-year period in a single center, with changes in practices and neonatal results during this period.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding breech presentation, we found that neonates delivered by CS had a lower risk of composite outcome of mortality or NDI compared with those delivered vaginally. Previous studies that have shown vaginal birth for preterm neonates in breech presentation is possibly associated with a higher risk of adverse neonatal outcomes, including mortality, BPD, ROP, and IVH compared with caesarean birth (10,45,46).…”
Section: Discussionmentioning
confidence: 93%